Research on cerebral palsy football: a scoping review - Bao, R.; Wang, X.; Shi, Y.; Ruano, M. Á. G. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Aim This study conducts the first scoping review in cerebral palsy (CP) football, a field that has received limited and uneven research attention. While the existing literature has primarily focused on aspects like match load and performance analysis, critical areas such as training interventions and health outcomes have not been consolidated or comprehensively reviewed. This review therefore aims to summarize available evidence, identify key research needs, and provide a comprehensive overview of existing knowledge.